Healing venous ulcers with different modalities of leg compression - Brizzio, E. O.; Blättler, W.; Rossi, G.; Chirinos, A.; Cantero, I.; Idiazabal, G.; Amsler, F. (Phlebologie, 2006)
Background: Compression therapy (CT) is the stronghold of treatment of venous leg ulcers. We evaluated 5 modalities of CT in a prospective open pilot study using a unique trial design. Patients and methods: A group of experienced phlebologists assigned 31 consecutive patients with 35 venous ulcers (present for 2 to 24 months with no prior CT) to 5 different modalities of leg compression, 7 ulcers to each group. The challenge was to match the modality of CT with the features of the ulcer in order to achieve as many healings as possible. Wound care used standard techniques and specifically tailored foam pads to increase local pressure. CT modalities were either stockings Sigvaris® 15-20, 20-30, 30-40 mmHg, multi-layer bandages, or CircAid® bandaging. Compression was maintained day and night in all groups and changed at weekly visits. Study endpoints were time to healing and the clinical parameters predicting the outcome. Results: The cumulative healing rates were 71%, 77%, and 83% after 3, 6, and 9 months, respectively. Univariate analysis of variables associated with nonhealing were: previous surgery, presence of insufficient perforating and/or deep veins, older age, recurrence, amount of oedema, time of presence of CVI and the actual ulcer, and ulcer size (p <0.05-<0.001). The initial ulcer size was the best predictor of the healing-time (Pearson r=0.55, p=0.002). The modality of CT played an important role also, as 19 of 21 ulcers (90%) healed with stockings but only 8 of 14 with bandages (57%; p=0.021). Regression analysis allowed to calculate a model to predict the healing time. It compensated for the fact that patients treated with low or moderate compression stockings were at lower risk of non-healing. and revealed that healing with stockings was about twice as rapid as healing with bandages. Conclusion: Three fourths of venous ulcers can be brought to healing within 3 to 6 months. Healing time can be predicted using easy to assess clinical parameters. Irrespective of the initial presentation ulcer healing appeared more rapid with the application of stockings than with bandaging. These unexpected findings contradict current believes and require confirmation in randomised trials.
Keywords: Chronic venous insufficiency; venous leg ulcers; compression therapy; medical compression stockings